Climate change adaptation through planted forages in Southern Highlands, Tanzania - Mukiri, Jessica; Notenbaert, An Maria Omer; Prestwidge, Di; Ash, Andrew J.; Paul, Birthe K. (International Center for Tropical Agriculture, 2019)
Smallholder farmers (SF) are the biggest food producers in Tanzania (TZ), where hetero- geneous mixed crop-livestock farming systems dominate agriculture (Fig 1). Feed scarcity and quality are major issues facing smallholder dairy farmers in Tanzania. Climate projections for Tanzania indicate increased length of dry seasons and severity of periodic droughts. These expected impacts will affect farm productivity, leaving farmers more vulnerable. The planting of improved grass and legume forages, if properly managed, has the potential to improve livestock productivity and resilience which can help SF adapt to climate change